Impaired oxidation of debrisoquine in patients with perhexiline neuropathy. Issue 6312 (30th January 1982) - Shah, R R; Oates, N S; Idle, J R; Smith, R L; Lockhart, J D
Abstract : The use of perhexiline maleate as an antianginal agent is occasionally associated with side effects, particularly neuropathy and liver damage. The reason why some individuals develop these toxic reactions is not clear, though some evidence suggests that they may result from impaired oxidative metabolism, due to genetic or hepatic factors, and consequential accumulation of the drug in toxic concentrations. Drug oxidation was measured with an oxidation phenotyping procedure in 34 patients treated with perhexiline, 20 of whom had developed neuropathy and 14 of whom had not. Most of the 20 patients with neuropathy, but not the unaffected patients, showed an impaired ability to effect metabolic drug oxidation. This impairment was independent of hepatic function, concurrent drug therapy, or tobacco or alcohol consumption. The fact that the ability to oxidise several drugs is genetically controlled points to a genetic susceptibility to developing neuropathy in response to perhexiline. Routine determination of the drug oxidation phenotype might lead to safer use of perhexiline by predicting patients who may be more at risk of developing a neuropathic reaction associated with its long-term use.